Influence of the rare-earths oxides doped on the SnO2CoOMnO2Ta2O5 varistor system - Dibb, A.; Tebcherani, S. M.; Lacerda, W.; Cilense, M.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Kluwer Academic Publ, 2002)
The tin dioxide is an n-type semiconductor, which exhibits varistor behavior with high capacity of absorption of energy, whose function is to restrict transitory over-voltages without being destroyed, when it is doped with some oxides. Varistors are used in alternated current fields as well as in continuous current, and it can be applied in great interval of voltages or in great interval of currents. The electric properties of the varistor depend on the defects that happen at the grain boundaries and the adsorption of oxygen. The (98.90-x)%SnO2.0.25%CoO+0.75%MnO2+0.05%Ta2O5+0.05%Tr2O3 systems, in which Tr=La or Nd. Current-voltage measurements were accomplished for determination of the non-linear coefficient were studied. SEM microstructure analysis was made to evaluate the microstructural characteristics of the systems. The results showed that the rare-earth oxides have influenced the electrical behavior presented by the system. (C) 2002 Kluwer Academic Publishers.